The processing and transferring of food in the colony of \(Odontotermes hainanensis\) Light (Isoptera: Macrotermitinae) - Thi My, Nguyen; Quoc Huy, Nguyen; Thuy Hien, Nguyen; Van Quang, Nguyen (Academia Journal of Biology, 2023)
Odontotermes hainanensis Light is known as a pest to structures, crops, dikes and dams in Vietnam that needs to be controlled. Currently, termite control using baits is considered a pre-eminent especially environmentally friendly measure. However, applying this method has been proven to be incapable to control O. hainanensis or other fungus-growing termites (subfamily Macrotermitinae) due to their complex food processing. The research on food processing and the food distribution ability within the colony of this species was conducted in order to identify a scientific basis to further enhance the efficiency when treating them with baits. Results on the food processing of laboratory cultured colonies showed that this process took from 21 to 35 days with labor division in worker groups. Results on food transferring by food marking method in the field colonies showed that food was distributed by workers to most of the fungus garden cavities of the colonies. The proportion of cavities that fungus combs containing marking food reached from 92.1% to 100% in these studied nests. This is an essential scientific basis for the termite bait study on controlling fungus-growing termites, particularly O. hainanensis.